A consensus statement on perinatal mental health during the COVID-19 pandemic and recommendations for post-pandemic recovery and re-build - Jackson, Leanne; Greenfield, Mari; Payne, Elana; Burgess, Karen; Oza, Munira; Storey, Claire; Davies, Siân M.; De Backer, Kaat; Kent-Nye, Flora E.; Pilav, Sabrina; Worrall, Semra; Bridle, Laura; et al. (Frontiers in Global Women's Health, 2024)
Introduction The COVID-19 pandemic posed a significant lifecourse rupture, not least to those who had specific physical vulnerabilities to the virus, but also to those who were suffering with mental ill health. Women and birthing people who were pregnant, experienced a perinatal bereavement, or were in the first post-partum year (i.e., perinatal) were exposed to a number of risk factors for mental ill health, including alterations to the way in which their perinatal care was delivered. Methods A consensus statement was derived from a cross-disciplinary collaboration of experts, whereby evidence from collaborative work on perinatal mental health during the COVID-19 pandemic was synthesised, and priorities were established as recommendations for research, healthcare practice, and policy. Results The synthesis of research focused on the effect of the COVID-19 pandemic on perinatal health outcomes and care practices led to three immediate recommendations: what to retain, what to reinstate, and what to remove from perinatal mental healthcare provision. Longer-term recommendations for action were also made, categorised as follows: Equity and Relational Healthcare; Parity of Esteem in Mental and Physical Healthcare with an Emphasis on Specialist Perinatal Services; and Horizon Scanning for Perinatal Mental Health Research, Policy, & Practice. Discussion The evidence base on the effect of the pandemic on perinatal mental health is growing. This consensus statement synthesises said evidence and makes recommendations for a post-pandemic recovery and re-build of perinatal mental health services and care provision.